Evaluation of the key geriatric assessment constructs in primary brain tumor population - a descriptive study. Issue 8 (November 2022) - Sass, Dilorom; Vera, Elizabeth; Choi, Anna; Acquaye, Alvina; Briceno, Nicole; Christ, Alexa; Grajkowska, Ewa; Jammula, Varna; Levine, Jason; Lindsley, Matthew; Reyes, Jennifer; Roche, Kayla; et al.
Abstract: Introduction: Despite an increasing aging population, older adults (≥ 65 years) with primary brain tumors (PBTs) are not routinely assessed for geriatric vulnerabilities. Recent reports of geriatric assessment (GA) in patients with glioblastomas demonstrated that GA may serve as a sensitive prognosticator of overall survival. Yet, current practice does not include routine evaluation of geriatric vulnerabilities and the relevance of GA has not been previously evaluated in broader cohorts of PBT patients. The objective of this descriptive study was to assess key GA constructs in adults with PBT dichotomized into older versus younger groups. Materials and Methods: A cross-sectional analysis of data collected from 579 participants with PBT recruited between 2016 and 2020, dichotomized into older (≥ 65 years, n = 92) and younger (≤ 64 years, n = 487) from an ongoing observational trial. GA constructs were evaluated using socio-demographic characteristics, Charlson Comorbidity Index (CCI), polypharmacy (>5 daily medications), Karnofsky Performance Status (KPS), Neurologic Function Score (NFS), and patient-reported outcome assessments including general health, functional status, symptom burden and interference, and mood. Descriptive statistics, t -tests, chi-square tests, and Pearson correlations were used to evaluate differences between age groups. Results: Older participants were more likely to have problems with mobility (58% vs. 44%), usual activities (64% vs 50%) and self-care (38% vs 26%) compared to the younger participants (odds ratios [ORs] = 1.3–1.4, ps < 0.05), while older participants were less likely to report feeling distressed (OR = 0.4, p < 0.05). Older participants also had higher CCI and were more likely to have polypharmacy (OR = 1.7, ps < 0.05). Increasing age strongly correlated with worse KPS score ( r = −0.232, OR = 1.4, p < 0.001) and worse NFS ( r = 0.210, OR = 1.5, p < 0.001). No differences were observed in overall symptom burden, symptom interference, and anxiety/depression scores. Discussion: While commonly used GA tools were not available, the study employed patient- and clinician-reported outcomes to identify potential future research directions for the use of GA in the broader neuro-oncology population. Findings illustrate missed opportunities in neuro-oncology practice and underscore the need for incorporation of GA into routine care of this population. Future studies are warranted to further evaluate the prognostic utility of GA and to better understand functional aging outcomes in this patient population.